2013
DOI: 10.1007/s11695-013-1094-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Adherence to Follow-Up Visits After Bariatric Surgery: Reasons and Outcome

Abstract: The nonadherence rate to follow-up visits after bariatric surgery was 17.5%, mainly associated with work-related problems. Nonadherence was greater in patients aged ≤45 years and in those with poor weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 25 publications
4
46
1
4
Order By: Relevance
“…Lost to follow-up data provide an insight into the potential utility of apps and the challenges faced by dietitians providing nutritional support to bariatric patients. When examining the reasons for attrition, our findings were similar to other studies, with the most common reasons being lack of weight loss and cost; however, the third most common reason given was the poor understanding by patients of the need for nutrition support (7,23) . Patients who do not recognise the need for lifelong dietary support from a dietitian often seek advice from elsewhere such as online.…”
Section: Discussionsupporting
confidence: 86%
“…Lost to follow-up data provide an insight into the potential utility of apps and the challenges faced by dietitians providing nutritional support to bariatric patients. When examining the reasons for attrition, our findings were similar to other studies, with the most common reasons being lack of weight loss and cost; however, the third most common reason given was the poor understanding by patients of the need for nutrition support (7,23) . Patients who do not recognise the need for lifelong dietary support from a dietitian often seek advice from elsewhere such as online.…”
Section: Discussionsupporting
confidence: 86%
“…Vidal et al [20] showed that nonadherence after surgery was associated with poor surgical results, especially in the first year. Furthermore, irregular life and diet style may also be important reasons for long-term surgical failure [20]. We emphasize the importance of improving follow-up rates and postoperative education to reduce the incidence of unsuccessful diabetes control.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a structured postoperative follow-up, including frequent clinical examination and investigation of the vitamin serum levels is very important. Several published studies confirmed, that many patients are not adherent to a follow-up program [4]. As described, a structured follow-up program after bariatric surgery is crucial to improve and sustain weight loss [5].…”
mentioning
confidence: 85%